2011
DOI: 10.1007/s12043-011-0098-z
|View full text |Cite
|
Sign up to set email alerts
|

The classification of single travelling wave solutions to the Camassa–Holm–Degasperis–Procesi equation for some values of the convective parameter

Abstract: By the complete discrimination system for the polynomial, we give the classification of single travelling wave solutions to the Camassa-Holm-Degasperis-Procesi equation for some values of the convective parameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…It is found that if a NLEE can be turned into an integral form then all possible exact solutions can be derived by this CDSPM [58]. Recently, this method has been used successively for solving many NLEEs [59][60][61][62]. Fan et al applied this method to find all possible exact travelling wave solutions to the generalized Pochhammer-Chree equation [63].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that if a NLEE can be turned into an integral form then all possible exact solutions can be derived by this CDSPM [58]. Recently, this method has been used successively for solving many NLEEs [59][60][61][62]. Fan et al applied this method to find all possible exact travelling wave solutions to the generalized Pochhammer-Chree equation [63].…”
Section: Introductionmentioning
confidence: 99%
“…[4] In the previous equation, the RHS represents dispersion and the value of the balance parameter was taken as b = 2. The Camassa-Holm-Degasperis-Procesi (CHDP) was introduced by Degasperis and Procesi [4] , also studied in [5]…”
Section: Introductionmentioning
confidence: 99%
“…into the equation of the coefficient corresponding to (ψ′(ξ)) −5 leads to, Solving the previous equations with the dispersion relation(5) leads to the following:…”
mentioning
confidence: 99%
“…By Liu's method, many nonlinear partial differential equations have been solved. For example, Wang and Li [10] used Liu's method and other methods to investigate the single and multi-solitary solutions to some nonlinear evolution equations; Wang et al [11] obtained the classification of traveling wave solutions to CH-DP equation; and, Fan [12] gave the classification of the single traveling wave solutions to the generalized equal width equation, and so on.…”
Section: Introductionmentioning
confidence: 99%